Student heterogeneity – the reality of the Sri Lankan ESL classrooms - Perera, M.E.S. (My University, 2008)
Student heterogeneity is the reality of the ESL classroom in Sri Lanka as well as in many Asian countries. Student heterogeneity is a problem teachers face in most classrooms. However, in the ESL secondary classrooms this problem is compounded due to the students’ prior experience or inexperience in L2. Students prior and current experience of L2 beyond the school is extremely diverse. Some of the students come from English speaking background homes and can easily converse in English. Some have no experience of English other than at school. These groups are further differentiated by their access to English teaching in the primary. Some of these students would have been taught English in the primary schools while others would not have been taught. Thus one of the problems identified in the ESL literature in Sri Lanka is the heterogeneity of the student population ( De Lanerolle Commission Report,1973; Jayasuriya, 1969; Karunaratne, 1990; Perera, 2002; Walatara, 1979) Despite this concern, there is little attention focused in teacher training or preparation of learning materials on how to cater to the different ability levels of the students. Nor are there any guidelines as to how to adapt the teaching procedures to cater for the different ability groups of students identified in Sri Lankan classrooms with regard to their English language proficiency(Karunaratne, 19990; perera,20002; Walatara,1979) The assumption is Sri Lanka that equal opportunities to learn English can be provided simply by using the same learning materials, based on the same teaching approach with all the students. Although this assumption has been challenged and the need for more classroom based ethnographic research to ease this problem has been emphasized (Perera, 2002) there is paucity of such research. This paper draws on classroom research data to describe how ability grouping was used successfully to address the issue of student heterogeneity . In one case study students werer grouped according to their language ability at entry to the secondary level Grade 7). These students were taught by different teachers in different classes according to students’ language ability using different learning materials. By providing a success-building lesson context to ‘scaffold’ these learners, they were able to progress to the higher ability level by the end of e secondary level (Grade11). The model used in this case study helped limit learner failing, and to create a supportive environment. The same model is currently being tried out in another school, within the same classroom to address student heterogeneity.